Análise de fluxo subterrâneo em interface mina a céu aberto e pilhas de rejeito em mineração de urânio por meio de investigação geofísica - Silveira, Ana Júlia Traiba da [UNESP] (2025)
Mining is one of the main sources of natural resources and economic development, however, it is responsible for the generation of several environmental liabilities that directly affect the quality of the biotic and abiotic environment. The Decommissioning Unit in Caldas (UDC) of Indústrias Nucleares do Brasil (INB), located in the Poços de Caldas Alkaline Complex, Minas Gerais, was the first ore extraction and processing unit to generate uranium concentrate, its activities began in 1982 and were permanently closed in 1995 as INB concluded it was economically unviable. Since then, the mine has been in the decommissioning phase, however, in the years in which the mine was in operation, several environmental liabilities were generated in the area, including Acid Mine Drainage (AMD), the environmental liability that most important for closure purposes, this environmental liability is capable of contaminating surface and underground water resources and has a high treatment cost. Therefore, with the aim of alleviating this problem, the Osamu Utsumi Mine implemented a Marginal Water Treatment Unit to treat this acid diversion. This process generates a residue called Calcium Diuranate, composed of metal hydroxides and which is destined for the open pit mine. So, this project aims to understand and diagnose the dense flows of these contaminants (AMD and Calcium Diuranate), at the interface of the uranium mine pit and the Bota Fora–08 (BF-08) tailings pile through the use of geophysics by the Electroresistivity method. To carry out and discuss this work, data obtained in the field were processed to produce 2D geophysical materials and 3D modeling, which were related to existing structural analysis data from the area. The 2D geophysical photos show the contrast between the flow zones and dry rock zones in the porous and fractured aquifer, which combined with the structural results corroborate the identification of the main preferential paths in the rock aquifer. The pseudo-3D models show that the low resistivities up to approximately 20m deep are the result of infiltration by DUCA and that from approximately 40m deep these values are the result of infiltration by DAM.